Bioclimatic conceptos and their applicability to andean rural area: San Francisco de Raymina community (SFR) case - Ayacucho - Espinoza, Rafael (2015)
An appropriate treatment of the problems that people, living in high Andean rural areas, have during the winter months with their cold houses, passes through a correct bioclimatic approach. This is demonstrated with the involvement of the Centre for Renewable Energy and the Faculty of Science of the National University of Engineering (UNI) in San Francisco de Raymina community (SFR) in Ayacucho. In this community a bioclimatic house has been built, allowing a thermal comfort of the occupants. This work has been done applying clearly and correctly bioclimatic concepts, some of which are presented in this article, as well as part of the experience of UNI in SFR community.